2018
DOI: 10.1159/000492962
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, but Not Hypertension and Obesity, Is Associated with Postoperative Cognitive Dysfunction

Abstract: Background/Aims: Older people undergoing surgery are at risk of developing postoperative cognitive dysfunction (POCD), but little is known of risk factors predisposing patients to POCD. Our objective was to estimate the risk of POCD associated with exposure to preoperative diabetes, hypertension, and obesity. Methods: Original data from 3 randomised controlled trials (OCTOPUS, DECS, SuDoCo) were obtained for secondary analysis on diabetes, hypertension, baseline blood pressure, obesity (BMI ≥30 kg/m2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
1
20
0
1
Order By: Relevance
“…It's been reported that through community experiments that higher blood pressure variability is related to the decline in cognitive function of patients assessed by simple mental status examination 46 . Although the systolic blood pressure variability cannot predict whether the risk of dementia in the overall population increases, it is not found in the subgroup of individuals without a history of cardiovascular disease 47 . The systolic blood pressure variability is positively correlated with the risk of dementia 48 .…”
Section: Discussionmentioning
confidence: 96%
“…It's been reported that through community experiments that higher blood pressure variability is related to the decline in cognitive function of patients assessed by simple mental status examination 46 . Although the systolic blood pressure variability cannot predict whether the risk of dementia in the overall population increases, it is not found in the subgroup of individuals without a history of cardiovascular disease 47 . The systolic blood pressure variability is positively correlated with the risk of dementia 48 .…”
Section: Discussionmentioning
confidence: 96%
“…Diabetes has the pathophysiological characteristics of inflammation, proliferation, and hypercoagulability. Diabetes is associated with higher stroke risk compared with diabetes-free persons ( 13 , 14 ). Diabetes causes various microvascular and macrovascular disorders often culminating in major clinical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there was no other control group in the general population that excludes normal cognitive changes. Thirdly, our study included a small proportion of diabetes which was associated with POCD [43] .…”
Section: Discussionmentioning
confidence: 99%